1982
DOI: 10.1530/jrf.0.0660625
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sheep fecundity by treatment with antisera to gonadal steroids

Abstract: T, 1\m=.\5for Group M and 1\m=.\0for the controls. The increase in the number of lambs born was due to a higher proportion giving birth to twins (P < 0\m=.\01); no ewe gave birth to triplets. High conception rates were recorded for all treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
4

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 14 publications
4
21
0
4
Order By: Relevance
“…In this study androstenedione binding activity was lower than that obtained in sheep (Land, Morris, Baxter, Fordyce and Forster, 1982). The immunization protocol used in the present study was similar to that reported previously in cattle, in which there was an increased ovulation rate.…”
Section: Discussionsupporting
confidence: 89%
“…In this study androstenedione binding activity was lower than that obtained in sheep (Land, Morris, Baxter, Fordyce and Forster, 1982). The immunization protocol used in the present study was similar to that reported previously in cattle, in which there was an increased ovulation rate.…”
Section: Discussionsupporting
confidence: 89%
“…The prevention of oestrus and ovulation by circulating antibodies to oestrogens has also been noted in other species (Sundaram, Tsong, Hood & Brinson, 1973;Ferin, Dyrenfurth, Cowchock, Warren & Vande Wiele, 1974;Elsaesser & Parvizi, 1977;Martin, Henricks, Hill & Rawlings, 1978;Elsaesser, 1980). Nevertheless, the increases in ovulation and lambing rates after immunization of sheep against oestrogens have been reported (Smith et ai, 1981 ;Land, Morris, Baxter, Fordyce & Forster, 1982). Since active or passive immunization with steroid hormones is now being considered for practical applications, the objectives of this study were to document the reproductive effects of active immunization of beef cattle against androstenedione and oestradiol-17ß (oestradiol) in relation to ovulation rates, conception rate, blood steroid hormones and ovarian morphology.…”
Section: Introductionmentioning
confidence: 86%
“…The antiserum (sheep 505) raised in sheep against testosterone-3-carboxymethyloxime (CMO) conjugated to egg albumen (Land et al, 1982) was used at a final dilution of 1:128 000. Gelatin phosphate buffer was used as RIA diluent and dextran-coated charcoal was used to separate the bound from the free testosterone.…”
Section: Methodsmentioning
confidence: 99%